Accelerated dehydrogenation kinetics through Ru, Fe dual-doped Ni2P as bifunctional electrocatalyst for hydrazine-assisted self-powered hydrogen generation. (January 2023) - Zhai, Xuejun; Yu, Qingping; Chi, Jingqi; Wang, Xinping; Li, Bin; Yang, Bo; Li, Zhenjiang; Lai, Jianping; Wang, Lei
Abstract: Seawater electrolysis is a potential way to realize the large-scale hydrogen production without relying on freshwater resources, but limited by the chlorine evolution reaction (ClER) on the anode and high potential for seawater electrolysis. In this work, MOF-derived Ru, Fe dual-doped Ni2 P nanosheets (RuFe-Ni2 P@NF) is constructed to serve as bifunctional catalyst for chlorine-free hydrogen production by hybrid hydrogen evolution reaction (HER) coupled with hydrazine oxidation reaction (HzOR) in seawater. As an ideal bifunctional electrocatalyst for overall hydrazine splitting (OHzS) in seawater, RuFe-Ni2 P@NF catalyst only needs 0.69 V to achieve 1000 mA cm −2 . Moreover, the energy-saving H2 production is realized by utilizing OHzS unit, which can save 4.70 W · h of electricity compared with the N2 H4 -free unit for producing 1.0 L of H2 . Moreover, the direct hydrazine fuel cell (DHzFC) is assembled to drive OHzS to realize the self-powered H2 production. The industrial hydrazine sewage can serve as feed for the above eletrolysis system, which has been degraded to ∼ 8 ppb rapidly. DFT calculations demonstrate that the Ru and Fe dual-doping can not only realize the thermoneutral ΔGH* for HER but also decrease the free energy of dehydrogenation of *N2 H3 to *N2 H2 for HzOR, realizing the intrinsically enhanced dehydrogenation kinetics. Graphical Abstract: In this work, Ru, Fe dual-doped Ni2 P nanosheets (RuFe-Ni2 P@NF) display high electrocatalytic activity and stability in seawater as bifunctional catalyst for hydrogen evolution reaction (HER) coupled with hydrazine oxidation reaction (HzOR). The direct hydrazine fuel cell (DHzFC) is assembled to drive OHzS to realize the self-powered H2 production. The industrial hydrazine sewage can serve as feed for the above eletrolysis system, which has been degraded to ∼ 8 ppb rapidly. DFT calculations demonstrate that the Ru and Fe dual-doping can not only realize the thermoneutral ΔGH* for HER but also decrease the free energy of dehydrogenation of *N2 H3 to *N2 H2 for HzOR, realizing the intrinsically enhanced dehydrogenation kinetics. ga1 Highlights: Ru, Fe dual-doped Ni2 P nanosheets (RuFe-Ni2 P@NF) with the typical nanosheet-like structure is in-situ grown on nickel foam. RuFe-Ni2 P@NF shows excellent HER, HzOR and overall hydrazine splitting (OHzS) performance in alkaline seawater. DFT demonstrate that dual-doping can realize the thermoneutral ΔGH* for HER and accelerate dehydrogenation for HzOR. The direct hydrazine fuel cell (DHzFC) is assembled to drive OHzS to realize the self-powered H2 production. The industrial hydrazine sewage can serve as feed for the eletrolysis system, which has been degraded to ∼8 ppb rapidly.